Synthesis, Reactivity and Stability of Aryl Halide Protecting Groups towards Di-Substituted Pyridines - Ptoton Mnangat Brian; Peter Musau (Indonesian Journal of Chemistry, 2016)
This paper reports the synthesis and reactivity of different Benzyl derivative protecting groups. The synthesis and stability of Benzyl halides, 4-methoxybenzyl halides, 3,5-dimethoxybenzyl halides, 3,4-dimethoxybenzyl halides, 3,4,5-trimethoxybenzyl halide protecting groups and their reactivity towards nitrogen atom of a di-substituted pyridine ring in formation of pyridinium salts is also reported.